2021
DOI: 10.1007/s10067-021-05839-9
|View full text |Cite
|
Sign up to set email alerts
|

Work absenteeism and disability associated with psoriasis and psoriatic arthritis in the USA—a retrospective study of claims data from 2009 TO 2020

Abstract: Objectives To compare work absenteeism and short-term disability among adults with psoriasis or psoriatic arthritis (PsA), versus controls in the USA. Methods Adults eligible for work absenteeism and/or short-term disability benefits between 1/1/2009 and 4/30/2020 were screened in the IBM® MarketScan® Commercial and Health and Productivity Management Databases. The following groups were defined: (1) psoriasis: ≥ 2 psoriasis diagnoses ≥ 30 days apart and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 36 publications
1
8
0
1
Order By: Relevance
“…Previous studies have measured the impact of PsA disease activity on patient productivity, 2,513 but a more developed understanding of treatment strategies and work absenteeism was needed. 29 Kavanaugh et al 18 showed a short-term, 24-week association between treating patients with PsA and improvements in productivity; this present study expanded on that work and found this improvement was sustained up to 4 years.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Previous studies have measured the impact of PsA disease activity on patient productivity, 2,513 but a more developed understanding of treatment strategies and work absenteeism was needed. 29 Kavanaugh et al 18 showed a short-term, 24-week association between treating patients with PsA and improvements in productivity; this present study expanded on that work and found this improvement was sustained up to 4 years.…”
Section: Discussionsupporting
confidence: 62%
“…This study helps with understanding how treatment strategies can improve productivity, which is needed not only from a clinical perspective, but also from an economic perspective. 29 Economic modelling of the disease impact of PsA has quantified the indirect cost of reduced patient productivity in the workplace and the household, 5,6,9,[14][15][16] and reported that a greater disease activity and lower utility is correlated with greater indirect costs. 41 Future economic modelling should consider improvements in productivity to develop an understanding of the indirect economic gain of achieving and maintaining greater levels of disease control with long-term therapy in this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…In almost one-third of cases, the consideration of productivity losses could have altered the final decision on whether to reimburse expensive drugs. This finding is unsurprising, given that a new drug in diseases such as psoriasis, arthritis or Crohn’s disease is likely being appraised owing to its considerable effectiveness and ability to alleviate the symptom burden, thus also reducing the amount of work loss seen with these disorders [ 46 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rising global burden of systemic rheumatic diseases (SRDs) manifests itself in mortality, disability-adjusted life expectancy [ 1 ], reduced quality of life [ 2 ] as well as direct and indirect health care costs, including absence from work and productivity [ 3 , 4 ]. The high demand of rheumatology care is opposed by an inadequate number of rheumatologists [ 5 ], resulting in diagnostic delays [ 6 ] and often consecutive irreversible damage [ 7 ].…”
Section: Introductionmentioning
confidence: 99%